PENGARUH KONDISI GEOGRAFIS TERHADAP HASIL BELAJAR SISWA DI SDN 01 SIMEGO - RUSWANDI RUSWANDI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
The purpose of this study was to determine the geographical conditions of Igir Gede hamlet, to determine student achievement (raport scores) obtained by the children of Igir Gede hamlet at SDN 01 Simego, and to determine the effect of geographical conditions on student achievement, namely the geographical condition of Igir Gede hamlet on learning achievement. students written in the report cards obtained by the children of the village of Igir Gede at SDN 01 Simego. This research is a type of correlation research. The population in this study are students in grades 1, 2, 3, 4, 5, and 6 at SDN 01 Simego from Igir Gede hamlet, totaling 40 children/students. There are two variables in this study, namely geographical conditions as variable X and student achievement as variable Y. Meanwhile, to analyze the data, the author uses the product momento correlation formula. Based on the research results, the geographical conditions of Igir Gede hamlet with an average score of 68.68 questionnaire scores (rounded to 69) are included in the 60-77 value interval, which is in the good category. Meanwhile, the student achievement (raport score) obtained by the children of the village of Igir Gede with an average value of 65.8 (rounded to 66) is included in the 63-81 score interval, namely the good category level. In the calculation of the product moment correlation, the value of r count = -0.07 (signed negative) Simple interpretation, the absolute value of the calculated r value | |= 0.07 is included in the value interval of 0.00-0.20 in the product moment table, which means that there is a negative correlation between geographical conditions and student achievement, but the negative correlation is very weak, so it is considered that there is no negative correlation. While a more careful interpretation, the absolute value of the calculated r = 0.07 rt = 0.312 at a significant level of 5% and the absolute value of the arithmetic value | | = 0.07 rt = 0.403 at a significant level of 1%. This means that between the geographical conditions of Igir Gede hamlet and student achievement (raport scores) obtained by the children of Igir Gede hamlet at SDN 01 Simego, Petungkriyono sub-district, Pekalongan district, there is no significant negative correlation. Thus, the hypothesis that the author proposes is not true. ABSTRAKTujuan penelitian ini adalah untuk mengetahui kondisi geografis dusun Igir Gede, mengetahui prestasi belajar siswa (nilai raport) yang diperoleh anak dusun Igir Gede di SDN 01 Simego, dan mengetahui pengaruh kondisi geografis terhadap prestasi belajar siswa, yaitu kondisi geografis dusun Igir Gede terhadap prestasi belajar siswa yang tertulis dalam raport yang diperoleh anak dusun Igir Gede di SDN 01 Simego. Penelitian ini merupakan jenis penelitian korelasi, populasi dalam penelitian ini adalah peserta didik kelas 1, 2, 3, 4, 5, dan 6 SDN 01 Simego yang berasal dari dusun Igir Gede yang berjumlah 40 anak/peserta didik. Adapun variabel dalam penelitian ini ada dua yaitu kondisi geografis sebagai variabel X dan prestasi belajar siswa sebagai variabel Y. Sedangkan untuk menganalisis data penulis menggunakan rumus korelasi product momento. Berdasarkan hasil penelitian kondisi geografis dusun Igir Gede dengan rata-rata skor nilai angket 68,68 (dibulatkan menjadi 69) masuk dalam interval nilai 60-77 yaitu kategori baik. Sedangkan prestasi belajar siswa (nilai raport) yang diperoleh anak dusun Igir Gede dengan nilai rata-rata 65,8 (dibulatkan menjadi 66) masuk dalam interval nilai 63-81 yaitu tingkatan kategori baik. Pada perhitungan korelasi product moment diperoleh nilai r hitung = -0,07 (bertanda negatif) Interpretasi secara sederhana, harga mutlak nilai r hitung ||= 0,07 masuk dalam interval nilai 0,00-0,20 tabel product moment yang artinya antara kondisi geografis dengan prestasi belajar siswa memang terdapat korelasi negatif tetapi korelasi negatif itu sangat lemah sehingga dianggap tidak ada korelasi negatif. Sedangkan interpretasi secara lebih cermat, harga mutlak nilai r hitung = 0,07rt = 0,312 pada taraf signifikan 5% dan harga mutlak nilai hitung hitung || = 0,07rt = 0,403 pada taraf signifikan 1%. Artinya antara kondisi geografis dusun Igir Gede dengan prestasi belajar siswa (nilai raport) yang diperoleh anak dusun Igir Gede di SDN 01 Simego kecamatan Petungkriyono kabupaten Pekalongan tidak terdapat korelasi negatif yang signifikan. Dengan demikian hipótesis yang penulis ajukan tidak benar.